Application of Deep Sea Water (DSW) for Nutrient Supplement in Hydroponics Cultivation of Tomato : Effect of supplemented DSW at Different EC Levels on Fruit Properties - Yudi Chadirin; Takahisa Matsuoka; Herry Suhardiyanto; Anas D. Susila (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2007)
Deep sea water (DSW) has the potential characteristics for nutrient supplement in hydroponics cultivation. This experiment was carried out to evaluate the application of DSW as a nutrient supplement for tomato cultivation in hydroponics system. Tomatoes were grown on 4 beds in nutrient film technique (NFT) system circulated with 1.5 dS m-1(control), 10 dS m-1 15 dS m-1 and 20 dS m-1 of nutrient solution, respectively.  DSW was supplemented into nutrient solution of control to obtain high EC level. Fresh weight of fruits decreased varied from 10-20% by increasing DSW concentration in nutrient solution, but the effect of the treatment was not found on size of 3rd truss fruits.  The density of fruits increased as the DSW concentration increased in nutrient solution. Tomato stiffness of treated plants had almost the same value among EC levels although different among 3 trusses.  Fruit quality parameters increased by increasing the DSW concentration in nutrient solution. Treated plants circulated with EC 20 dS m-1 supplemented nutrient solution for 2 weeks produced tomatoes with highest soluble solids, 8.0% Brix or increased 30% of control (1st truss).  However there were no significant effect on fruits of 2nd and 3rd trusses.  DSW could be used as nutrient supplement for hydroponics cultivation of tomato.     Key words :   Deep sea water, fruit quality, electrical conductivity, tomato